Reduced graphene oxide/congo red-molecular imprinted polymer organic thin film transistor for serine detection - Nurul Farhanah Ab Halim (School of Materials Engineering, 2016)
The research objectives are to synthesize rGO-CR-MIP for sensing material; to fabricate TIPS - Pentacene OTFT for biosensor transducer; to evaluate the characteristic of rGO-CR-MIP OTFT biosensor performance when it's exposed to serine analyte.